Structure Modification of Cinnamic Acid to (E)-1-(3,4-dihydroisoquinoline-2(1H)-yl)-3-phenylprop-2-en-1-one and Antioxidant Activity Test by DPPH Method - Pangaribowo, Dian Agung; Fathunnisa, Fathunnisa; Nugraha, Ari Satia; Puspaningtyas, Ayik Rosita; Sary, Indah Purnama (Borneo Journal of Pharmacy, 2024)
Antioxidants can protect cells from free radical damage by stabilizing them. One of the compounds that has antioxidant activity is cinnamic acid. Cinnamic acid and its derivatives have several activities: antibacterial, anticancer, and antioxidant. However, the ability of cinnamic acid to capture free radicals is still relatively low. One of the efforts that can be made to increase the antioxidant activity of cinnamic acid is to modify its structure. Structure modification is an effort to improve the pharmacological activity of a compound through chemical synthesis reactions. The cinnamic acid structure can be modified by changing the carboxylic -OH group into an amine group through an N-atom acylation reaction. This study was conducted by reacting cinnamoyl chloride (1a), which is a cinnamic acid derivative with 1,2,3,4-tetrahydroisoquinoline (2b) which is a compound of isoquinoline group to produce (E)-1-(3,4-dihydroisoquinoline-2(1H)-yl)-3-phenylprop-2-en-1-one (3b) and then tested for antioxidant activity using DPPH method. The resulting product compound was yellow crystals with a yield of 81.56%. The antioxidant activity produced by the product is more significant than that of cinnamic acid compounds at the same concentration.